Performance evaluations and stress: Field evidence of the hormonal effects of evaluation frequency - Frimanson, Lars; Hornbach, Janina; Hartmann, Frank G.H. (Accounting, Organizations and Society, 2021)
Accounting studies document that performance evaluations may cause evaluatees to experience job-related stress and suggest there is a positive relationship between the frequency of such evaluations and stress. In this paper we aim to modify this suggestion. Since performance evaluations also involve a periodic discharge of accountability for evaluatees, we expect that low evaluation frequency may cause stress as well. Drawing on the neurobiological literature on allostatic load, we argue that the prolonged anticipatory threat of being held accountable adds to stress buildup over time. Such buildup is often not consciously experienced but shows in hormonal patterns that are associated with delayed job-related dysfunctions such as burnout. We conducted a one-year field experiment, in which we observed enhanced stress-hormone levels (cortisol and thyrotropin) in participants assigned to a 12-week performance evaluation cycle compared to participants remaining in a 6-week cycle. We found no corresponding difference between conditions on self-reported mental fatigue. This confirms our expectation and suggests that adopting a neurobiological view of job-related stress provides a complementary account of the effect of performance evaluation on both immediately experienced and delayed manifestations of job-related stress.